The Profitability and Risk Effects of Russian Banking Institutions’ Involvement in Bancassurance: Merger Simulation Methodology - Ekimov, Alexander V. (Ekonomika, 2018)
This paper presents the methodology taken to evaluate the potential profitability and risk effects of Russian banking institutions’ involvement in bancassurance. An original methodology is applied, which was developed by Boyd and Graham, to conduct merger simulations between commercial banks and insurance companies. The methodology is based on mergers between firms, like the accounting principle of consolidation by pooling. This principle entails summing up the balance-sheet indicators of previously independent firms to simulate a hypothetical merger.